Culturing intestinal stem cells: applications for colorectal cancer research - Fujii, Masayuki; Sato, Toshiro (Frontiers in Genetics, 2014)
Recent advance of sequencing technology has revealed genetic alterations in colorectal cancer. The biological function of recurrently mutated genes has been intensively investigated through mouse genetic models and colorectal cancer cell lines. Although these experimental models may not fully reflect biological traits of human intestinal epithelium, they provided insights into the understanding of intestinal stem cell self-renewal, leading to the development of novel human intestinal organoid culture system. Intestinal organoid culture enabled to expand normal or tumor epithelial cells in vitro retaining their stem cell self-renewal and multiple differentiation. Gene manipulation of these cultured cells may provide an attractive tool for investigating genetic events involved in colorectal carcinogenesis.